S‐Adenosyl Methionine Cofactor Modifications Enhance the Biocatalytic Repertoire of Small Molecule C‐Alkylation. (21st October 2019) - McKean, Iain J. W.; Sadler, Joanna C.; Cuetos, Anibal; Frese, Amina; Humphreys, Luke D.; Grogan, Gideon; Hoskisson, Paul A.; Burley, Glenn A.
Abstract: A tandem enzymatic strategy to enhance the scope of C ‐alkylation of small molecules via the in situ formation of S ‐adenosyl methionine (SAM) cofactor analogues is described. A solvent‐exposed channel present in the SAM‐forming enzyme SalL tolerates 5′‐chloro‐5′‐deoxyadenosine (ClDA) analogues modified at the 2‐position of the adenine nucleobase. Coupling SalL‐catalyzed cofactor production with C ‐(m)ethyl transfer to coumarin substrates catalyzed by the methyltransferase (MTase) NovO forms C ‐(m)ethylated coumarins in superior yield and greater substrate scope relative to that obtained using cofactors lacking nucleobase modifications. Establishing the molecular determinants that influence C ‐alkylation provides the basis to develop a late‐stage enzymatic platform for the preparation of high value small molecules. Abstract : Eine enzymatische Tandemstrategie zur Erweiterung des Umfangs der C‐Alkylierung kleiner Moleküle durch Verknüpfung der Produktion von S‐Adenosylmethionin (SAM)‐Cofaktoranaloga mit C‐Methyl‐/Ethyltransfer auf Cumarinsubstrate, katalysiert durch die Methyltransferase (MTase) NovO, wird beschrieben. Im Vergleich zu Cofaktoren ohne Nukleobase‐Modifikationen werden C‐methylierte/ethylierte Cumarine mit höherer Ausbeute und größerem Substratumfang gebildet.